2012 45th Hawaii International Conference on System Sciences 2012
DOI: 10.1109/hicss.2012.456
|View full text |Cite
|
Sign up to set email alerts
|

On Tuning the Knobs of Distribution-Based Methods for Detecting VoIP Covert Channels

Abstract: Abstract-We study the parameters (knobs) of distributionbased anomaly detection methods, and how their tuning affects the quality of detection. Specifically, we analyze the popular entropy-based anomaly detection in detecting covert channels in Voice over IP (VoIP) traffic.There has been little effort in prior research to rigorously analyze how the knobs of anomaly detection methodology should be tuned. Such analysis is, however, critical before such methods can be deployed by a practitioner. We develop a prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The "cost" for the extra reliability is a loss of some fraction of the steganographic bandwidth. Arackaparambil et al [2012] described a simple VoIP steganography method in which chosen RTP packets' payloads are replaced with a steganogram and the RTP header's sequence number, and/or timestamp fields are intentionally changed to make them appear as if they were excessively delayed by the network. This solution can be treated as a variation of the LACK method described above.…”
Section: Hybrid Methods (S3)mentioning
confidence: 99%
See 1 more Smart Citation
“…The "cost" for the extra reliability is a loss of some fraction of the steganographic bandwidth. Arackaparambil et al [2012] described a simple VoIP steganography method in which chosen RTP packets' payloads are replaced with a steganogram and the RTP header's sequence number, and/or timestamp fields are intentionally changed to make them appear as if they were excessively delayed by the network. This solution can be treated as a variation of the LACK method described above.…”
Section: Hybrid Methods (S3)mentioning
confidence: 99%
“…Experimental results showed that the subspace-based model proved to be very simple and yielded very good performance, while the convex set-based one was more powerful, but more timeconsuming. Arackaparambil et al [2012] analysed how in distribution-based steganalysis, the length of the window of the detection threshold and in which the distribution is measured, should be depicted to provide the greatest chance for success. The results obtained showed how these two parameters should be set for achieving a high rate of detection, whilst maintaining a low rate of false positives.…”
Section: Voip Steganalysismentioning
confidence: 99%
“…Arackaparambil et al analyzed how, in distribution‐based steganalysis, the length of the window of the detection threshold and in which the distribution was measured should be depicted to provide the greatest chance of success. The results obtained showed how these two parameters should be set for achieving a high rate of detection, while maintaining a low rate of false positives.…”
Section: Related Workmentioning
confidence: 99%
“…We assume that for the purposes of this paper it is not crucial which steganogram spreading mechanism is used, and thus it is out of the scope of this work. (1), typically transcoded (2), and encoded with covert codec (3) The performance of TranSteg depends, most notably, on the characteristics of the pair of codecs: the overt codec originally used to encode user speech and the covert codec utilized for transcoding. In ideal conditions the covert codec should not significantly degrade user voice quality compared to the quality of the overt codec (in an ideal situation there should be no negative influence at all).…”
Section: Introductionmentioning
confidence: 99%